Voiding symptoms aggravate with decreasing stromal/epithelial ratio and increasing glandular-epithelial content in patients undergoing laser enucleation for benign prostatic hyperplasia, independently from prostate size - Patrick Keller; Sheng Hu; Wenbin Zhu; Yajie Xu; Laurenz Berger; Philip Nicola; Philipp Weinhold; Alexander Tamalunas; Christian G. Stief; Martin Hennenberg (PLoS ONE, 2026)
Introduction Benign prostatic hyperplasia (BPH) includes epithelial, stromal and mixed hyperplasia, but their specific contributions to voiding symptoms and prostate volume (PV) are unknown. Here, we examined relationships of symptoms and PV with stromal and epithelial markers in patients undergoing laser enucleation for BPH. Methods Tissues were obtained from holmium or thulium laser enucleation of the prostate (n = 146 patients). Expressions of the smooth muscle marker calponin-1 (CNN1) and the glandular-epithelial cell marker keratin-19 (KRT19) were assessed by RT-PCR and Western blot, and analyzed for correlation with international prostate symptom score (IPSS), maximum urinary flow rate (Q max ), and PV. Results The ratio of CNN1/KRT19 mRNA correlated positively with Q max (r = 0.3809, p = 0.0263), and by trend negatively with IPSS (r = −0.2161, p = 0.0944). Accordingly, the IPSS increased with keratin protein expression (r = 0.4244, p = 0.0307), while the Q max tended to correlate negatively with keratin expression (r = −0.2058, p = 0.4999). PV correlated negatively with CNN1 mRNA expression (r = −0.205, p = 0.0405). The inverse correlation of CNN1 with PV persisted in patients without catheterization (r = −0.2568, p = 0.0457), but was lacking in catheterized patients after separated analyses. Conclusions Voiding symptoms in patients undergoing laser enucleation for BPH aggravate with increasing keratin content. Symptoms in patients needing surgery for BPH depend rather on glandular-epithelial hyperplasia, but not on stromal hyperplasia, what might explain why these patients are refractory to treatment with α 1 -blockers.